An integrated model of stomatal development and leaf physiology. Issue 4 (19th November 2013) - Dow, Graham J.; Bergmann, Dominique C.; Berry, Joseph A.
Summary: Stomatal conductance ( g s ) is constrained by the size and number of stomata on the plant epidermis, and the potential maximum rate of g s can be calculated based on these stomatal traits (Anatomical g smax ). However, the relationship between Anatomical g smax and operational g s under atmospheric conditions remains undefined. Leaf‐level gas‐exchange measurements were performed for six Arabidopsis thaliana genotypes that have different Anatomical g smax profiles resulting from mutations or transgene activity in stomatal development. We found that Anatomical g smax was an accurate prediction of g s under gas‐exchange conditions that maximized stomatal opening, namely high‐intensity light, low [CO2 ], and high relative humidity. Plants with different Anatomical g smax had quantitatively similar responses to increasing [CO2 ] when g s was scaled to Anatomical g smax . This latter relationship allowed us to produce and test an empirical model derived from the Ball–Woodrow–Berry equation that estimates g s as a function of Anatomical g smax, relative humidity, and [CO2 ] at the leaf. The capacity to predict operational g s via Anatomical g smax and the pore‐specific short‐term response to [CO2 ] demonstrates a precise link between stomatal development and leaf physiology. This connection should be useful to quantify the gas flux of plants in past, present, and future CO2 regimes based upon the anatomical features of stomata. Abstract : See also the Commentary by Franks and Casson